Transcription of the Stationary-Phase-Associated hspX Gene of Mycobacterium tuberculosis Is Inversely Related to Synthesis of the 16-Kilodalton Protein - Hu, Yanmin (American Society for Microbiology, 1999)
The 16-kDa protein, an α-crystallin homologue, is one of the most abundant proteins in stationary-phase Mycobacterium tuberculosis. Here, transcription and translation of the hspX gene, which encodes the 16-kDa protein, have been investigated by Northern blotting analysis, primer extension, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis with a microaerophilic stationary-phase model. Two transcripts of about 2.5 and 1.1 kb were demonstrated by Northern blot analysis and hybridized to the hspX gene probe. Primer extension analysis revealed that the transcription start site is located 33 nucleotides upstream of the hspX gene start codon. The cellular level of the hspX mRNA was maximum in log-phase bacilli and was markedly reduced after 20 days in unagitated culture, when the organisms had entered the stationary phase. A third transcript of 0.5 kb was detected 0.6 kb downstream of the hspX gene; this transcript has a transcriptional pattern completely different from that of the 1.1- and 2.5-kb products, suggesting that there may be another gene in this region. In contrast to the high level of hspX mRNA in log-phase bacilli, 16-kDa protein synthesis was low in log-phase bacteria and rose to its maximum after 20 days. In both log-phase and stationary-phase bacteria the mRNA was unstable, with a half-life of 2 min, which indicated that the transcript stability was growth rate independent and not a general means for controlling the gene expression. However, the cellular content of 16-kDa protein, while low in log-phase bacteria, rose to a maximum at 10 days and remained at this high level for up to 50 days, which indicates that this protein is a stable molecule with a low turnover rate. These data suggest that the regulation of hspX expression during entry into and maintenance of stationary phase involves translation initiation efficiency and protein stability as potential mechanisms.